THE EFFECTS OF PRAGMATIC INSTRUCTION ON THE PRAGMATIC AWARENESS AND PRODUCTION OF KOREAN UNIVERSITY STUDENTS - Kim, Hyekyeng (Indonesian Journal of Applied Linguistics, 2017)
Despite the ongoing research of interlanguage pragmatics, intervention studies concerning pragmatic instruction have not been conducted as actively. The present study aims to investigate the effects of pragmatic instruction on Korean university students specifically regarding compliment responses. The effects of the instruction were examined in terms of the students' pragmatic awareness and production, according to the various language proficiency levels of the students. A total of 106 Korean university students from various majors participated in the study. The experimental group received explicit pragmatic instruction, which entailed metapragmatic instruction, awareness raising activities, and output practice regarding compliment responses, whereas the control group was exposed to the target features with no explicit instruction. A set of pragmatic awareness questionnaire and discourse completion tasks were administered as the data collection instruments and an eclectic design was adopted to analyze the effects of the instruction regarding their pragmatic awareness and production. The results indicate that explicit pragmatic instruction provided positive effects for raising the level of pragmatic awareness in the low group. Additionally, both the intermediate and low groups showed a significant improvement in production, as confirmed by the examination between and within subjects, and also displayed a range of formulaic expressions with a less idiosyncrasy attributed to first language transfer. These results call for further attention to pragmatics in second language (L2) teaching and learning.Â